Pengembangan Model Kemitraan UMKM dengan Usaha Skala Sedang dan Besar di Jawa Timur Melalui Program Corporate Social Responsibility (CSR) - Herrukmi Septa Rinawati; FX Sri Sadewo (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2019)
Micro, Small and Medium Enterprises (UMKM) in Indonesia are contributors to national economic growth. In East Java itself, the number of MSMEs is relatively large. However, there are still many obstacles in its development, such as the ineffective partnership pattern, and the development is not as expected. Therefore, this study aims to determine the implementation of the partnership model between MSME entrepreneurs with medium and large scale businesses that have been running so far, the involvement of local governments in implementing the partnership model, obstacles encountered in implementing the partnership model, as well as how to develop the MSME partnership model with medium and large scale business. The method used in this study is a mix method (qualitative and quantitative). The results showed that the implementation of the partnership model between MSME entrepreneurs with medium and large scale businesses so far has been enhanced by involving companies through the Corporate Social Responsibility (CSR) program. Local government involvement is also through regulations with the concept of partnership of MSME entrepreneurs with medium and large companies. Obstacles faced including coordination between stakeholders is still not optimal. By increasing MSME partnerships with medium and large businesses it is expected to overcome existing obstacles such as limited resources.